Secure Payment Methods in Export-Import Transactions - Gunardi Lie; Fayola Bearminta Chandra (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
International trade involves high payment risks due to differences in location, legal systems, and lack of trust between exporters and importers. This study aims to identify the parties involved in the Letter of Credit (L/C) mechanism and to analyze why L/C is considered a safer payment method. The research uses an empirical method with a descriptive qualitative approach through literature study. The results show that L/C involves several parties, including importers, exporters, issuing banks, and advising/negotiating banks, supported by other parties such as customs and insurance companies. L/C is considered safer because payment is guaranteed by the bank and only made after all required documents are fulfilled. Therefore, L/C provides security and certainty in international trade transactions.